2014
DOI: 10.3221/igf-esis.30.13
|View full text |Cite
|
Sign up to set email alerts
|

Elastic compliance of single-edge-notched tension SE(T) (or SENT) specimens

Abstract: There has been a trend recently to use specimen geometries for toughness measurement that are more representative of actual flaw geometries in service. A prominent example is the use of single-edge-notched tension specimens for assessment of surface flaws in pipelines. To obtain a resistance (R) curve, i.e. J-integral or CTOD as a function of crack growth, it is necessary to monitor the crack size as a function of J or CTOD. To facilitate obtaining these data from a single specimen, the elastic CMOD unloading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…As can be seen above, the differences are very small. This is in accordance to the observations made by Tyson et al [11] and Wang et al [9]. Table 4 shows a comparison between the final crack measurements; a p,C and a p,S are the final calculated crack lengths according to Cravero's and Shen's equation respectively, a p is the measured crack length according to the nine points average method as proposed by ASTM E 1820 [5].…”
Section: Crack Growthsupporting
confidence: 86%
See 2 more Smart Citations
“…As can be seen above, the differences are very small. This is in accordance to the observations made by Tyson et al [11] and Wang et al [9]. Table 4 shows a comparison between the final crack measurements; a p,C and a p,S are the final calculated crack lengths according to Cravero's and Shen's equation respectively, a p is the measured crack length according to the nine points average method as proposed by ASTM E 1820 [5].…”
Section: Crack Growthsupporting
confidence: 86%
“…The 8th order polynomial, although more cumbersome, does have a larger interval of validity (0.05≤a/W≤0.95). A comparative study performed by Tyson et al [11], determined a very small difference between the two definitions in an interval of 0.1≤a/W≤0.8. Wang et al [9] also noted a small difference between the two methods, although they concluded that the 5 th order polynomial as proposed by Cravero was the most precise.…”
Section: Unloading Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Tyson et al [16] suggest that it is because the constraint for the bulk of the specimen is closer to plane stress than to plane strain, although the crack tip constraint is close to plane strain. Tyson et al [16] suggest that it is because the constraint for the bulk of the specimen is closer to plane stress than to plane strain, although the crack tip constraint is close to plane strain.…”
Section: + Y/eb^cimentioning
confidence: 99%
“…þ 83:52325u 4 À 39:11201u 5 ; 0:1 a=W 0:7 (9) Note that in the corresponding original publications, 18-23 E 2D was taken as E in Eqs (6a)- (8), and E′ in Eqs (5a), (5b) and (9). Several studies 20,26,28 have revealed that using E instead of E′ in Eqs (5a), (5b) and (9) can lead to more accurate predictions of a/W for specimens with B/W = 1. Based on this, E 2D was set to equal E in Eqs (5a)- (9) in the present study.…”
mentioning
confidence: 99%